Following Saizarbitoria’s intertextual paths: an analysis of the novel Martutene - Urkiza Sánchez, Asier (EGAN, 2022)
The purpose of this article is to analyze the intertextual resources of the novel Martutene, published in 2013 by Ramon Saizarbitoria. Characters, scenes or symbols of other Saizarbitorias works can be found in the text, deepening the writers natural tendency to repetition. Moreover, the novel is full of intertex- tual quotes and references and it is possible to find traces of many authors there. Among those all it stands out the novel Montauk, written by Max Frisch. It can be asserted that it works as an hipotext of Martutene. Within the explicit level can be found the presence of other authors, Xabier Lizardi and Miguel de Unamuno, for instance. Finnaly, regarding to the implicit references and using the concept of intertext reader, we can point out its relation with Philip Roths novel American Pastoral.